2018
DOI: 10.1007/s10068-018-0414-1
|View full text |Cite
|
Sign up to set email alerts
|

Oligopeptide derived from solid-state fermented cottonseed meal significantly affect the immunomodulatory in BALB/c mice treated with cyclophosphamide

Abstract: In this study, the immunomodulatory activity of oligopeptide (CP) derived from solid-state fermented cottonseed meal were investigated in immunosuppressed BALB/c mice models by treatment with cyclophosphamide (CY). Results indicated that oligopeptide increased the thymus and spleen indices of CY-treated mice. The count of plague forming cells (PFC) and the content of half serum hemolysis (HC50) in immunosuppressive mice were restored to the normal level in CP-10 and CP-20 groups while the cytokines interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…Thymus and spleen functions can be evaluated by thymus index and spleen index [29]. The previous research indicated that polysaccharide can increase the thymus index and spleen index, and enhance the immune function of mice [30,31]. The results of this study showed that the thymus index and spleen index of mice increased after MHFP treatment, and the effect is a dosedependent manner.…”
Section: Discussionmentioning
confidence: 61%
“…Thymus and spleen functions can be evaluated by thymus index and spleen index [29]. The previous research indicated that polysaccharide can increase the thymus index and spleen index, and enhance the immune function of mice [30,31]. The results of this study showed that the thymus index and spleen index of mice increased after MHFP treatment, and the effect is a dosedependent manner.…”
Section: Discussionmentioning
confidence: 61%
“…Macrophages synthesize IL-1β in response to inflammatory signals, which further trigger the production of other inflammatory cytokines such as IL-6 in target cells. This synergistically promotes and amplifies the inflammatory response leading to tissue damage [49,50]. Thus, TNF-α, IL-1β, and IL-6 were used to evaluate the immunomodulatory and anti-inflammatory effects of the compound.…”
Section: Resultsmentioning
confidence: 99%
“…The potential elimination of ANFs by SSF is important for increasing the economic value and for making it possible for CAM to be well utilized as animal feed or food products in the food and feed industries. The beneficial effect of SSF in improving the nutritive value and bioactivity of various oilseed meals such as rapeseed meal [10], canola meal [13], soybean meal [14] and cottonseed meal [15] using different types of microorganisms have been previously reported. In an earlier study, CAM treated with Saccharomyces cerevisiae (yeast) was found to contain reduced phytic acid content compared to the unfermented control [16].…”
Section: Introductionmentioning
confidence: 96%